COVID 19 PANDEMIC IMPACT ON DIAGNOSING AND TREATMENT OF ADULT GLAUCOMA PATIENTS IN SERBIA - Bozic, Marija (Medical Research, 2023)
Aim. The aim of this study is to summarize the continuity of diagnostic procedures and surgical treatment of patients with glaucoma during the first two years of the COVID 19 pandemic in the tertiary ophthalmology center of the Republic of Serbia - the Clinic for Eye Diseases of the University Clinical Center of Serbia, and to compare it to the period before the declaration of the pandemic. Material and methods. In this retrospective study, we collected data from the protocol of performed diagnostic procedures – visual field testing, optical coherence tomography and clinical examinations, as well as from the protocol of the operating theatre. Results. The number of examined patients, the number of diagnostic procedures related to glaucoma, as well as the number of laser interventions and glaucoma surgeries (trabeculectomy) decreased from 20 to 66 percent during the period of the COVID 19 pandemic. Conclusions. The COVID 19 pandemic has led to a drastic reduction in the number of examinations, laser interventions and surgeries for people suffering from glaucoma.